The Voice of Hope: Aung San Suu Kyi Conversations with Alan Clements - ฉิมพะเนาว์, มุกรวี (วารสารพุทธอาเซียนศึกษา, 2022)
The Voice of Hope: Aung San Suu Kyi is the series of 13 interviews with Aung San Suu Kyi who is the leader of the struggle for human rights and democracy in Burma. She is the daughter of Aung San, who led the fight against Japan and England until Burma gained independence. He was later assassinated in 1947 and is regarded as Burma's independence hero.